HIZBUT TAHRIR SEBAGAI GERAKAN SOSIAL (Pengaruh Hizbut Tahrir di Timur Tengah Terhadap HTI di Indonesia) - , Khusnul Khotimah, S.Th.I.; , Prof. Dr. M. Abdul Karim, M. A., M. A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
From the first time Hizbut Tahrir (HT) born on 1953 in Al-Quds Palestine, this organization has a big idea to run Islamic life and perform Islamic proselytizing to all around the world. To upright Islamic values in society life, Hizbut Tahrir (HT) has a conviction to do it through the state by emphasize it to Daulah Islamiyah or Daulah Khilafah which lead by a khalifah chosen democratically by populace. The khalifah need to be Baiâat by Muslim community to be listened and obedient in order to run Islamic governance based on Kitabullah and sunnah of the rasul and develop Islamic precept to all around the world by Islamic proselytizing and Jihad. The development of Islam community has to be reached by enlightening and educating, for that HT try to bring back Islam communityâs position to the glorious age like it has ever happened in the past. From here, the study about HT in this research is begun. The born of Hizbut Tahrir Indonesia pioneered by some of HTâs members and sympathizers those have directly in touch with this movement in Middle East. So it is not wonder if name, type, doctrine, ideology, and the movement methods are absolutely follow HT in Middle East. This research is aimed to know the history and development of HT until its first emerged in Indonesia